PROBLEM - SOLVING AND DEVELOPING HUMAN RIGHTS CASES ARE GUIDELINES FOR PROTECTING AND PROMOTING HUMAN RIGHTS: A CASE STUDY OF GATHERING THE EVIDENCE - Wisetsin, Chattamat (Journal of MCU Nakhondhat, 2024)
This research aims to study and analyze foreign laws as guidelines for solving the problem of gathering evidence or obtaining evidence from victims during investigation stage of human trafficking cases. The study employed the qualitative research method with the documentary research approach by studying and collecting relevant information from local and foreign books, research papers, textbooks and journals on issues related to evidence collection or obtaining evidence from victims during investigation stage of Thailand’s human trafficking cases. Information gathered from the data collection were analyzed to seek answers to research problems as a guideline in developing a model of gaining international acceptance of Thailand’s human trafficking cases leading to effective prevention and suppression of human trafficking in the future. The study found the following results. 1) The United Kingdom’s human trafficking cases had guidelines for coordination between prosecutors and police. The police must coordinate with the prosecutor to collect evidence and ensure sufficient evidence presented to the court. The role of the prosecutor was to offer advice to the police in the investigation stage from the beginning of the investigation. It caused an appropriate and balance examination as a guideline for developing the human trafficking investigation process and collaboration between the prosecutor and the police effectively. 2) The Federal Republic of Germany determined that the prosecutor monitored the investigation. Therefore, the evidence presented in the witnesses investigation stage of the court was examined from the beginning. This is a great advantage that Thailand should apply.